Functional impact of CD161 on T cells - Smith, K (2013)
Human CD161 is protein that is expressed by most Natural Killer (NK) cells, of T cells (including both CD4+ and CD8+ subsets), Natural Killer T (NKT) cells and immature thymocytes. CD161 is expressed on many of the T cell receptor (TCR) expressing cell types that “bridge” both the innate and the adaptive immune systems, including mucosal associated invariant T (MAIT) cells. Changes in expression levels of CD161 in peripheral blood or tissue have been seen in multiple disease states such as: HIV, tuberculosis, multiple sclerosis, rheumatoid arthritis and psoriasis. However, the functional role of CD161 on T cells was unclear. Therefore, this thesis explores the impact of CD161 ligation on CD8+ T cells. CD161 surface expression was seen to be significantly downregulated upon ligation with its receptor (LLT1) or cross-linked by anti-CD161 antibodies. Despite this, no clear functional impact of CD161 ligation was seen on resting CD8+ Va7.2+ cells. In contrast, ligation of CD161 on TCR stimulated CD8+ Va7.2+ cells resulted in increased IFNy and TNFa expression, cell activation and cytotoxicity. The increased cytotoxicity was potentially due to both an increase in the ability of the cells to degranulate and the expression of Granzyme B. Furthermore, ligation of CD161 induced an increase in activated Caspase 3 expression, indicating increased apoptosis. CD161 ligation over a prolonged period resulted in a decrease in proliferation. In total these results suggest that CD161 acts as a co-stimulatory molecule for T cells in the context of TCR activation.